Lactobacillus genomics and metabolic engineering - Ruzal, Sandra M. (CAISTER ACADEMIC Press, 2019)
The considerable commercial importance has stimulated a plethora of research projects studying the genomics, molecular biology and metabolic engineering of these bacteria and prompted the need for this concise book which provides a timely overview of the field. Topics covered include: the genomic perspective on niche adaptability; catabolic pathways of complex carbohydrates metabolism; the production of lactate; genetics, biology of the cell envelope and applications of the S-layer proteins; lactobacilli bacteriophage; DNA transfer into Lactobacillus species; recombinant gene expression and ge.